PERAN PERPUSTAKAAN MASJID RAYA SUMATERA BARAT SEBAGAI SUMBER BELAJAR ADAT MINANGKABAU - Nupin, Iswadi Syahrial; Yassin, Beni Adri (Institut Agama Islam Negeri Salatiga, 2024)
A mosque library is an institution or work unit that manages written works, printed works and/or recorded works professionally using a standard system, which was formed and developed by the mosque to meet research, knowledge, information, religious and recreational needs. As an informal educational institution, the West Sumatra Grand Mosque Library should provide printed books, especially about Minangkabau Customs. This is due to the small number of printed books on the subject of Minangkabau Customs. The aim of this research is to describe the role of the West Sumatra Grand Mosque Library as a Minangkabau Traditional Learning Resource and to describe the supporting and inhibiting factors of the West Sumatra Grand Mosque Library as a Minangkabau Traditional Learning Resource. The research method used is a qualitative method. Qualitative research is a type of research that produces insights that cannot be achieved using statistical or other quantitative methods. The results of this research indicate that the West Sumatra Grand Mosque Library cannot be said to be a source of learning about Minangkabau Customs. This is due to the low level of visits to the library and the relatively small collection held by the West Sumatra Grand Mosque Library. Other obstacles found in the management of the West Sumatra Grand Mosque Library are the absence of definitive management staff, the absence of a fixed budget, relatively small collections, the membership system has not yet been established and the absence of donors or institutions that provide book grant assistance and the promotion of POCADI (Pojok Baca Digital) by the Sumatra Grand Mosque Library has not yet been implemented. West to the residents of the city of Padang.